THE USE OF GOOGLE SITES MEDIA IN LEARNING AT MADRASAH IBTIDAIYAH MA'ARIF LABSCHOOL SINTANG DURING THE COVID-19 PANDEMIC - Nandi Supriyanto; Muhammad Faisal; Bayu Purnama Aji; Hadisa Putri (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2021)
The purpose of this research in general is to find out the use of google sites media in learning at Madrasah Ibtidaiyah Ma'arif Labschool Sintang during the covid-19 pandemic. Specific objectives, namely: 1) To find out the use of google sites media during the covid-19 pandemic. 2) To find out the use of google sites media during the covid-19 pandemic. 3) To find out the factors supporting and inhibiting the use of google sites media at Madrasah Ibtidaiyah Ma'arif Labschool Sintang during the covid-19 pandemic. This type of research is classified as field research, with the research approach used is descriptive. The data sources for this study were fiqh teachers and coconuts at Madrasah Ibtidaiyah Ma'arif Labschool Sintang. Furthermore, the data collection methods used were interviews and documentation. Furthermore, data processing and analysis techniques were carried out through four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. This research is a qualitative research that focuses on the use of google media sites in Madrasah Ibtidaiyah Ma'arif Labschool Sintang. The research population is all residents of Madrasah Ibtidaiyah Ma'arif Labschool Sintang. The research sample is Islamic Religious Education Teachers. The results of this study indicate that the use of google sites media makes learning easier because in it it can be done attendance, assign assignments and save syllabus and share interesting videos such as animated cartoons and will definitely be liked by students. For face-to-face learning, it can be done using google meet by means of video calls where the teacher can provide material virtually to students, teachers and students can see each other. For how to use Google Sites, it's quite easy just by logging into Google and then going to Sites provided you already have an email, everyone can enter Google Sites as long as you have a valid email. to verify users of these sites so that users of these sites